Preparation method and application of high-entropy catalyst tellurium selenium tungsten molybdenum sulfide
By preparing the high-entropy catalyst tungsten sulfide molybdenum tellurium selenium sulfide, the problems of polysulfide shuttle effect and redox kinetics in lithium sulfur batteries are solved, and higher energy density and longer cycle life are achieved.
Patent Information
- Application Number
- CN202411591677.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Lithium sulfur batteries have challenges in the shuttle effect of polysulfides, volume changes of electrode materials, and slow redox kinetics, and traditional single-component or two-component catalysts have limited effects.
The preparation method of the high entropy catalyst tungsten sulfide molybdenum tellurium selenium sulfide is used to dissolve selenium powder, sodium molybdate dihydrate, tungsten chloride and thiourea in a reduced graphene oxide suspension, and then undergo hydrothermal reaction and annealing treatment. Form a high entropy catalyst with surface rich in active sites.
It improves the transmission efficiency of ions and electrons, enhances the dynamic performance of the battery, extends the cycle life of the lithium-sulfur battery, and increases the energy density.
Smart Images

Figure CN119390020A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to a preparation method of a high entropy catalyst tungsten molybdenum telluride selenide and an application thereof. Background Art
[0002] Energy issues are one of the major challenges facing the world, including energy supply security, climate change and environmental pollution. In this context, lithium-ion batteries, as an efficient and rechargeable energy storage technology, have become an important tool for solving energy problems. With the growing global demand for sustainable energy, the improvement of their performance and materials has become the focus of scientific research. Among them, lithium-sulfur (Li-S) batteries have become a powerful alternative to traditional lithium-ion batteries due to their high theoretical energy density, low cost and abundance of sulfur resources. The chemical reaction of Li-S batteries involves reversible electrochemical reactions between lithium and sulfur, and has the potential to store more energy than traditional battery technology. However, to fully realize the potential of Li-S batteries and make them commercially available, some challenges need to be addressed, mainly including the shuttle effect of polysulfides, volume changes of electrode materials, and slow redox kinetics. Although traditional single-component or two-component catalysts can improve these problems to some extent, their effects are often unsatisfactory due to the inherent limitations of a single material. In contrast, high-entropy catalysts, due to their rich active sites and highly disordered crystal structure brought by their multi-combination, can promote electrochemical reactions under a wider range of conditions and show catalytic activity and stability beyond conventional materials. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation method and application of a high-entropy catalyst tungsten molybdenum telluride selenide. The diversified element combination inside the high-entropy catalyst forms a complex electron transfer path, which is conducive to the rapid transmission of electrons, thereby improving the transmission efficiency of ions and electrons and enhancing the kinetic performance of the battery.
[0004] To achieve the above object, the present invention provides a method for preparing a high entropy catalyst of tellurium selenide tungsten molybdenum sulfide, comprising the following steps: S1, adding selenium powder to hydrazine hydrate solution to form solution A; S2, dissolving sodium molybdate dihydrate, tungsten chloride and thiourea in the reduced graphene oxide suspension to form a mixed solution B; S3, mixing solution A and solution B together and stirring to obtain solution C, and transferring solution C to an autoclave for hydrothermal reaction; S4, washing the product obtained by the reaction with deionized water, and freeze-drying after washing to obtain a black product A; S5. Place product A at the downwind side of the tubular furnace, and place tellurium powder at the upwind side of the tubular furnace, and perform annealing treatment in an argon-hydrogen environment to obtain a tellurium-selenium-tungsten-molybdenum sulfide catalyst.
[0005] Preferably, the mixing temperature of the selenium powder and the hydrazine hydrate solution in S1 is 50-100°C, the purity of the selenium powder is >99.99%, the particle size is <75µm, and the purity of the hydrazine hydrate is analytical grade.
[0006] Preferably, the purity of sodium molybdate dihydrate in S2 is >99%, the purity of tungsten chloride is >99%, the purity of thiourea is >99.9%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.
[0007] Preferably, in S3, the stirring time is 0.25-3 h, the stirring temperature is 40-80° C., the temperature of the hydrothermal reaction is 160-250° C., and the reaction time is 10-30 h.
[0008] Preferably, the mass ratio of tellurium powder to product A in S5 is 1:2-0.1, the annealing temperature is 400-800° C., and the annealing time is 1-6 h.
[0009] Preferably, the concentrations of selenium powder, sodium molybdate dihydrate and tungsten thiourea chloride in solution C are all 2-8 mmol / mL.
[0010] Preferably, the volume percentage content of hydrazine hydrate in solution C is 10-50%.
[0011] Preferably, the mass percentage of the single elements S, Se, Te, W and Mo in the tellurium selenide tungsten molybdenum sulfide catalyst is 10-80%.
[0012] The present invention also provides an application of a high entropy catalyst tungsten molybdenum telluride selenide. The tungsten molybdenum telluride selenide catalyst prepared by the above-mentioned preparation method of a high entropy catalyst tungsten molybdenum telluride selenide is used as a positive electrode material to prepare a lithium-sulfur battery.
[0013] Therefore, the present invention adopts the above-mentioned high entropy catalyst tungsten molybdenum telluride selenide preparation method and application, which has the following beneficial effects: (1) The present invention combines the chalcogen elements Te, Se, S with W and Mo to form a high-entropy catalyst. The surface of the high-entropy catalyst is rich in various types of active sites, which can strongly adsorb and catalyze polysulfides, reduce the so-called shuttle effect, and promote the conversion of polysulfides, accelerating their electrochemical redox reactions. Secondly, the presence of multiple metal elements leads to changes in the d orbital energy level, enhancing the adsorption strength and selectivity of the catalyst for polysulfides, thereby optimizing its catalytic performance. In addition, the special structures (such as edges, defects, grain boundaries, etc.) formed on the surface of the high-entropy catalyst provide additional active sites, significantly accelerating the reaction rate. The combination of diversified elements forms a complex electron transfer path, which is conducive to the rapid transmission of electrons, thereby improving the transmission efficiency of ions and electrons and enhancing the kinetic performance of the battery. The synthesized catalyst has important practical application value in lithium-sulfur batteries.
[0014] (2) The preparation method of the present invention obtains a high entropy catalyst of tellurium selenide tungsten molybdenum sulfide through simple and mild solution treatment and hydrothermal reaction, and the surface has a large number of defects. The defect concentration and the tellurium selenide tungsten molybdenum sulfide ratio are controllable, and the defect concentration and the tellurium selenide tungsten molybdenum sulfide ratio can be controlled by adjusting the reaction time, temperature, the amount of tellurium selenide tungsten molybdenum sulfide source and other conditions.
[0015] (3) After being prepared into a lithium-sulfur battery, the tellurium selenide tungsten molybdenum sulfide catalyst of the present invention has higher adsorption and catalytic activity for different polysulfides, higher energy density and longer cycle life than lithium-sulfur batteries prepared with a single catalyst. Under 0.2C conditions, the initial capacity is 1159 mAh·g -1 , the capacity retention rate after 200 cycles is about 81.3%, showing great potential in lithium-sulfur batteries.
[0016] (4) The preparation method of the tellurium selenide tungsten molybdenum sulfide catalyst of the present invention is simple and easy to operate, does not require complicated instruments and equipment, uses tellurium selenide sulfide and tungsten molybdenum sources as synthetic materials, is inexpensive compared to catalyst materials containing precious metals, and is suitable for industrial production.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanning electron microscope (SEM) image of a tungsten-molybdenum-telluride-selenide catalyst prepared in Example 1 of a method for preparing a high-entropy catalyst tungsten-molybdenum-telluride-selenide and its application; Figure 2 This is a method for preparing a high entropy catalyst tungsten molybdenum telluride selenide and its application Example 1 of the present invention. The element distribution diagram of the tungsten molybdenum telluride selenide catalyst prepared under a scanning electron microscope; Figure 3 The present invention discloses a method for preparing a high entropy catalyst tungsten molybdenum telluride selenide and its application. The constant current charge and discharge curves of a battery prepared using the tungsten molybdenum telluride selenide catalyst prepared in Example 1 and Comparative Examples 1 and 2 as positive electrode materials at a current of 1C. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0020] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0021] The present invention provides a high entropy catalyst tellurium selenide tungsten molybdenum sulfide, which has a layered nanosheet morphology, grows uniformly on redox graphene, and produces abundant defects. The preparation method thereof comprises the following steps: S1. Add selenium powder to hydrazine hydrate solution to form solution A, wherein the mixing temperature of selenium powder and hydrazine hydrate solution is 50-100°C, the purity of selenium powder is >99.99%, the particle size is <75µm, and the purity of hydrazine hydrate is analytical grade.
[0022] S2. Dissolve sodium molybdate dihydrate (Na2MoO4·2H2O), tungsten chloride (WCl) and thiourea in the reduced graphene oxide suspension (rGO) to form a mixed solution B, wherein the purity of sodium molybdate dihydrate is >99%, the purity of tungsten chloride is >99%, the purity of thiourea is >99.9%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.
[0023] S3. Solution A and solution B are mixed together and stirred at 40-80°C for 0.25-3h to obtain solution C, and solution C is transferred to an autoclave for hydrothermal reaction. The temperature of the hydrothermal reaction is 160-250°C, the reaction time is 10-30h, the volume percentage content of hydrazine hydrate in solution C is 10-50%, and the concentrations of selenium powder, sodium molybdate dihydrate, and tungsten thiourea chloride in solution C are all 2-8mmol / mL.
[0024] S4, washing the product obtained by the reaction with deionized water, and freeze-drying after washing to obtain a black product A; S5. Place product A downwind of the tubular furnace, and place tellurium powder upwind of the tubular furnace, and perform annealing treatment in an argon-hydrogen environment. The annealing temperature is 400-800° C., and the annealing time is 1-6 hours to obtain a tellurium-selenium tungsten-molybdenum sulfide catalyst. The mass ratio of tellurium powder to product A is 1:2-0.1. The ratio of S, Se, Te, W, and Mo in the tellurium-selenium tungsten-molybdenum sulfide catalyst is adjustable, and the mass percentage of a single element is 10-80%.
[0025] The present invention combines the chalcogen elements Te, Se, S with W and Mo at the same time to form a high entropy compound catalyst tellurium selenide tungsten molybdenum sulfide. The surface of the high entropy catalyst is rich in various types of active sites, which can strongly adsorb polysulfides (LiPSs) to prevent them from dissolving and shuttling in the electrolyte, thereby reducing the so-called "shuttle effect", which is one of the main reasons for the performance degradation of lithium-sulfur batteries.
[0026] At the same time, high entropy catalysts can promote the conversion of polysulfides to Li2S, accelerate their electrochemical redox reactions, and improve the cycle efficiency and energy output of batteries. Secondly, the presence of multiple metal elements in high entropy materials leads to the complexity of the electronic structure, especially the change of d orbital energy levels, which can effectively regulate the electronic state of the catalyst. This regulation of the d band center can enhance the adsorption strength and selectivity of the catalyst for polysulfides, thereby optimizing its catalytic performance.
[0027] In addition, the special structures formed on the surface of high-entropy catalysts (such as edges, defects, grain boundaries, etc.) provide additional active sites, which are particularly important for catalyzing the redox reaction of polysulfides and can significantly accelerate the reaction rate. The combination of diversified elements inside the high-entropy catalyst forms a complex electron transfer path, which is conducive to the rapid transmission of electrons, thereby improving the transmission efficiency of ions and electrons and enhancing the kinetic performance of the battery.
[0028] Example 1 The invention provides a preparation method of a high entropy catalyst tellurium selenide tungsten molybdenum sulfide, comprising the following steps: first, at 70°C, 0.75 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate, 0.75 mmol of tungsten chloride and 0.75 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed together and stirred for 15 minutes to obtain solution C, and solution C is transferred to a Teflon autoclave and stored at a temperature of 200°C for 24 hours. The product obtained by the reaction is washed with deionized water and freeze-dried to obtain a black product A. Finally, a tubular furnace is used for annealing treatment, 3 mmol of tellurium powder is placed in an upwind position, and product A is placed in a downwind position, and annealing treatment is performed at 550°C in an argon hydrogen environment for 2 hours to obtain a tellurium selenide tungsten molybdenum sulfide catalyst.
[0029] Figure 1 As shown in the scanning electron microscope (SEM) image of Example 1, the tungsten molybdenum telluride selenide sulfide layered nanosheets prepared in Example 1 grow uniformly on the redox graphene, and the average size is about 100 nm.
[0030] Figure 2This is the element distribution diagram of scanning electron microscope in Example 1. It shows the uniform distribution of S, Se, Te, W and Mo elements on rGO nanosheets, confirming that S, Se, Te, W and Mo were successfully introduced.
[0031] Example 2 The invention provides a preparation method of a high entropy catalyst tellurium selenide tungsten molybdenum sulfide, comprising the following steps: first, at 70°C, 1.5 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate, 1.5 mmol of tungsten chloride and 0.75 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed together and stirred for 15 minutes to obtain solution C, and solution C is transferred to a Teflon autoclave and stored at a temperature of 200°C for 24 hours. The product obtained by the reaction is washed with deionized water and freeze-dried to obtain a black product A. Finally, a tubular furnace is used for annealing treatment, 2 mmol of tellurium powder is placed in an upwind position, and product A is placed in a downwind position, and annealing treatment is performed at 600°C in an argon hydrogen environment for 2 hours to obtain a tellurium selenide tungsten molybdenum sulfide catalyst.
[0032] Example 3 The invention provides a preparation method of a high entropy catalyst tellurium selenide tungsten molybdenum sulfide, comprising the following steps: first, at 70°C, 0.75 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate, 1 mmol of tungsten chloride and 1.5 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed together and stirred for 15 minutes to obtain solution C, and solution C is transferred to a Teflon autoclave and stored at a temperature of 200°C for 24 hours. The product obtained by the reaction is washed with deionized water and freeze-dried to obtain a black product A. Finally, a tubular furnace is used for annealing treatment, 5 mmol of tellurium powder is placed in an upwind position, and product A is placed in a downwind position, and annealing treatment is performed at 700°C in an argon hydrogen environment for 2 hours to obtain a tellurium selenide tungsten molybdenum sulfide catalyst.
[0033] Comparative Example 1 Compared with Example 1, solution A is not required, tungsten chloride does not need to be added to solution B, the product obtained by hydrothermal treatment is annealed at 550° C. in a tube furnace under the protection of argon, and the other steps remain the same to obtain a molybdenum disulfide catalyst.
[0034] Comparative Example 2 Compared with Example 1, solution A is not required, and sodium molybdate dihydrate does not need to be added to solution B. The product obtained by hydrothermal treatment is annealed at 550° C. in a tube furnace under the protection of argon, and the other steps remain the same to obtain a tungsten disulfide catalyst.
[0035] In order to evaluate the effectiveness of the tellurium selenide tungsten molybdenum sulfide catalyst in actual lithium-sulfur batteries, sulfur was incorporated into the catalysts prepared in Comparative Example 1, Comparative Example 2 and Example 1 by conventional melt impregnation method to form a sulfur cathode and prepare a battery. The experimental steps are as follows: the synthesized catalyst is combined with sulfur by grinding and then heated in an inert atmosphere at 155°C for 12 hours. Subsequently, the active material (70%), polyvinylidene fluoride (PVDF, 10%) and carbon black (20%) are dissolved in N-methylpyrrolidone (NMP) to prepare a slurry. The slurry is then coated on aluminum foil and dried in a vacuum oven at 60°C for 12 hours. The dried coated foil is cut into sheets with a diameter of 10 mm. The cathodes synthesized in Comparative Example 1, Comparative Example 2 and Example 1 are S@MoS2 / rGO, S@WS2 / rGO and S@WMoSSeTe / rGO, respectively.
[0036] Figure 3 The performance diagram of the battery prepared by the composite materials of Comparative Example 1, Comparative Example 2 and Example 1, the battery was cycled under 1C conditions. The discharge capacity of the S@WMoSSeTe / rGO-based battery prepared in Example 1 is 1159 mAh·g -1 , exceeding the S@MoS2 / rGO-based battery in comparative example 1 (824 mAh g -1 ) and the S@WS2 / rGO-based battery of Comparative Example 2 (997 mAh·g -1 ) performance. This is because the special structures formed on the surface of high-entropy catalysts (such as edges, defects, grain boundaries, etc.) provide additional active sites, significantly accelerating the reaction rate. The combination of diversified elements forms a complex electron transfer path, which is conducive to the rapid transmission of electrons, thereby improving the transmission efficiency of ions and electrons and enhancing the kinetic performance of the battery.
[0037] Therefore, the present invention adopts the preparation method and application of the above-mentioned high entropy catalyst tellurium selenide tungsten molybdenum sulfide, and the surface of the prepared high entropy catalyst tellurium selenide tungsten molybdenum sulfide is rich in various types of active sites, which can strongly adsorb and catalyze polysulfides, reduce the so-called shuttle effect, and promote the conversion of polysulfides, and accelerate the electrochemical redox reaction thereof; secondly, the presence of multiple metal elements leads to changes in d orbital energy levels, enhances the adsorption strength and selectivity of the catalyst for polysulfides, and thus optimizes its catalytic performance; in addition, the combination of diversified elements forms a complex electron transfer path, which is conducive to the rapid transmission of electrons, thereby improving the transmission efficiency of ions and electrons and enhancing the kinetic performance of the battery.
[0038] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high entropy catalyst of tellurium, selenium, tungsten and molybdenum sulfide, characterized in that: The following steps are involved: S1, adding selenium powder to hydrazine hydrate solution to form solution A; S2, dissolving sodium molybdate dihydrate, tungsten chloride and thiourea in the reduced graphene oxide suspension to form a mixed solution B; S3, mixing solution A and solution B together and stirring to obtain solution C, and transferring solution C to an autoclave for hydrothermal reaction; S4, washing the product obtained by the reaction with deionized water, and freeze-drying after washing to obtain a black product A; S5. Place product A at the downwind side of the tubular furnace, and place tellurium powder at the upwind side of the tubular furnace, and perform annealing treatment in an argon-hydrogen environment to obtain a tellurium-selenium-tungsten-molybdenum sulfide catalyst.
2. The method for preparing a high entropy catalyst of tellurium, selenium, tungsten, molybdenum sulfide according to claim 1, characterized in that: The mixing temperature of selenium powder and hydrazine hydrate solution in S1 is 50-100°C, the purity of selenium powder is >99.99%, the particle size is <75µm, and the purity of hydrazine hydrate is analytical grade.
3. The method for preparing a high entropy catalyst of tellurium, selenium, tungsten, molybdenum sulfide according to claim 2, characterized in that: The purity of sodium molybdate dihydrate in S2 is >99%, the purity of tungsten chloride is >99%, the purity of thiourea is >99.9%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.
4. The method for preparing a high entropy catalyst of tellurium, selenium, tungsten, molybdenum sulfide according to claim 3, characterized in that: In S3, the stirring time is 0.25-3h, the stirring temperature is 40-80°C, the temperature of the hydrothermal reaction is 160-250°C, and the reaction time is 10-30h.
5. The method for preparing a high entropy catalyst of tellurium, selenium, tungsten, molybdenum sulfide according to claim 4, characterized in that: The mass ratio of tellurium powder to product A in S5 is 1:2-0.1, the annealing temperature is 400-800°C, and the annealing time is 1-6h.
6. The method for preparing a high entropy catalyst of tellurium, selenium, tungsten and molybdenum sulfide according to claim 5, characterized in that: The concentrations of selenium powder, sodium molybdate dihydrate and tungsten thiourea chloride in solution C are all 2-8 mmol / mL.
7. The method for preparing a high entropy catalyst of tellurium, selenium, tungsten, molybdenum sulfide according to claim 6, characterized in that: The volume percentage content of hydrazine hydrate in solution C is 10-50%.
8. The method for preparing a high entropy catalyst of tellurium, selenium, tungsten, molybdenum sulfide according to claim 7, characterized in that: The mass percentage of the single elements S, Se, Te, W and Mo in the tellurium selenide tungsten molybdenum sulfide catalyst is 10-80%.
9. Application of a high entropy catalyst of tellurium, selenium, tungsten and molybdenum sulfide, characterized in that: The tungsten molybdenum telluride selenide catalyst prepared by the method for preparing a high entropy catalyst tungsten molybdenum telluride selenide as described in claim 8 is used as a positive electrode material in the preparation of a lithium-sulfur battery.
Citation Information
Patent Citations
Molybdenum diselenide / carbon black composite hydrogen evolution electro-catalysis material and preparation method thereof
CN105132941A
Surface-amphiphilic nano tungsten molybdenum sulfide hydrogenation catalyst, preparation method and application thereof
CN105498805A
Molybdenum sulfide / molybdenum selenide composite material and preparation and application thereof
CN106099053A
Molybdenum (tungsten) diselenide (disulfide) / carbon composite material as well as preparation method and application thereof
CN106816602A
Method for preparing 1T / 2H-phase MoSSe in hydrothermal mode
CN109183065A